Three-dimensional analysis of intracycle velocity fluctuations in frontcrawl - Psycharakis, S. G.; Naemi, R.; Connaboy, C.; McCabe, C.; Sanders, R. H. (Scandinavian Journal of Medicine & Science in Sports, 2010)
The purpose of this study was to determine accurately the magnitude and changes of intra-cycle velocity fluctuation (Vfluc), maximum (Vmax) and minimum velocity (Vmin) of the center of mass during a maximum 200 m frontcrawl swim, and to examine whether they are associated with performance. Performance was indicated by the mean velocity (Vmean) of the stroke cycle (SC) in the swimming direction. The relative Vfluc, Vmax and Vmin were also calculated as a percentage of Vmean, while Vfluc was calculated for all three directions. Eleven male swimmers of national/international level participated in this study and their performance was recorded with four below- and two above-water-synchronized cameras. Four SCs were analyzed for the 200 m swim (one for each 50 m). Anthropometric data were calculated by the elliptical zone method. Vmean generally decreased throughout the test. Vmax and Vmin were positively correlated to performance and were significantly higher in SC1 than in the other SCs. However, the relative Vmax and Vmin values were remarkably consistent during the 200 m and not associated with performance. Despite the noteworthy magnitude of Vfluc in all directions, they were in general not correlated with performance and there were no significant changes during the test.